The geology of the Miami Mica field (Urungwe District) - Wiles, J W (Rhodes University, Faculty of Science, Department of Geology, 1961)
[Preface] The detailed geological survey of the country described in this bulletin commenced in 1953 and was completed in 1956 with the mapping of 1,480 square miles of country. Information is supplied on 227 mines which produced mica alone or both mica and beryl, and 134 mines which produced only beryl. In addition, wolfram, gold, graphite, kyanite and rutile deposits and mines are described. Mineral outputs are given up to end of 1959. The field mapping and writing of the bulletin is entirely the work of Mr. Wiles. Mapping of the Field has established that, with a few exceptions, a metamorphic control has operated in the development of economic sheet mica and has led to the conclusion that very many of these pegmatites are composite bodies which have derived their material from two sources: one metamorphic and the other igneous. This conclusion was arrived at after a detailed petrographic investigation of the metamorphic rocks. The map at the end of this bulletin was drawn by Mr.A. H. Barrie and the diagrams are largely the work of Mr. D. O. L. Levy. Chemical analyses are by Messrs. A. J. Radford and E. Golding and were made in the Geological Survey Laboratory. Some of the photographs are by H. J. Cotterel of the Geological Survey while the remainder were taken by the Planning and Technical Services of the Federal Ministry of Home Affairs (formerly the Federal Information Department). It gives me pleasure to acknowledge the assistance and facilities offered the Department by mining men and residents in the district.
Keywords: Geology -- Zimbabwe -- Urungwe District; Mines and mineral resources -- Zimbabwe -- Urungwe District; Mica -- Zimbabwe -- Urungwe District